Stories of Developing Critical Praxes: Introspections into Coaches' Learning Journeys - Kramers, Sara (Université d'Ottawa / University of Ottawa, 2024)
Competitive youth sport does not occur in a vacuum, and societal changes impact coaches' practices. Researchers have called for a paradigm shift for coaches to become more socially responsible and adopt a critical praxis. The purpose of this dissertation was to advance our current understanding of critical praxis development within competitive youth sport, through narrative introspections into coaches' learning journeys. Anchored in cultural sport psychology research, this dissertation was guided by a relativist ontology, a social constructionist epistemology, and narrative inquiry methodology. The critical positive youth development framework (Gonzalez et al., 2020) was used to explore coaches' critical praxes and critical consciousness development in sport. In Article 1, I explored coaches' challenges and successes in creating safer and more inclusive sport spaces. The coaches felt responsible for enacting change in sport while questioning when it was okay to intervene, feeling burnt out, and finding success with their critical actions. Composite creative nonfictions were developed to reflect the individual and shared experiences in developing their critical praxes as coaches. The coaches shared a desire for in-situ support for unpacking their biases and understanding complicated social issues in sport. In Article 2, a 15-month collaboration is detailed, whereby I acted as a personal learning coach to support a competitive Nordic ski coach's (Sophie) critical praxis as they reflected on social issues and acted to enact positive change in their sport context and community. As suggested by Rodrigue and Trudel (2019), my role as a personal learning coach was guided by the narrative-collaborative coaching approach (Stelter, 2014) to focus on Sophie's narratives and co-create knowledge. From working together during two competitive seasons, Sophie's learning journey is presented through time hopping snapshot vignettes as they figured out what to fight for, grew through discomforts and unknowns, and experienced progress in their critical consciousness-building. An autoethnographic account is presented in Article 3 to detail how I 'ran with' becoming a personal learning coach for two competitive youth sport coaches, Sophie and Zoe. Through reflexive, evocative, and analytical writing, three salient experiences are presented, including how I used my 'full' biography to be(come) a personal learning coach, focused on the intricacies of relationality, and learned how to understand my limits as a researcher-participant acting as a personal learning coach. The complexities involved in co-learning between researchers and coaches are narratively explored. Collectively, this dissertation contributes to cultural sport psychology research with the use of the critical positive youth development framework and the narrative-collaborative coaching approach to explore coaches' varying levels of critical consciousness. Through creative analytical practices, narratives are shared of coaches' who are working to create safer, more inclusive competitive sport spaces. Researchers, sport leaders, and coaches are all responsible for looking inwards, challenging biases and assumptions, and advocating for a transformed competitive youth sport system that is safer and more inclusive for all.
Keywords: Competitive youth sport; Social justice; Creative analytical practices; Narrative inquiry; Coach learning; Critical consciousness